IMPLEMENTATION OF MARKETING PUBLIC RELATIONS STRATEGIES IN INCREASING THE EXISTENCE OF SAYURBOX - Arisnandhy, Doni; Tomohardjo, Irmulansati; Ridaryanthi, Melly (Universitas Mercu Buana, 2025)
In the era of global competition, companies are required to enhance performance and business activities. Marketing plays a crucial role, yet extensive promotions incur significant costs. The internet and online shopping have transformed businesses, particularly e-grocery. Sayurbox leverages digital platforms but faces challenges like changing consumer behavior and layoffs due to mismatched target markets. Companies must build a strong reputation beyond product quality. MPR acts as a bridge between companies and consumers. This study analyzes MPR implementation in enhancing Sayurbox's existence. The research methodology employs a qualitative approach with a case study. Data was collected through interviews with the public relations manager, and five consumers of Sayurbox. The implementation of Marketing Public Relations (MPR) by Sayurbox includes structured PR strategies, a focus on positive image building through company values, and transparent crisis management. Effective communication strategies are used for new product launches. Sayurbox adopts a combination of pull, push, and pass strategies to expand market reach. Pull strategies emphasize customer interaction via social media and events. Push strategies include promotions, bundle deals, loyalty programs, and endorsements. Pass strategies involve community relations and social responsibility. Strong negotiation skills are also a key advantage.